The impact of colorectal surgery on health-related quality of life in older functionally dependent patients with cancer – A longitudinal follow-up study. Issue 5 (September 2019) - Souwer, Esteban T.D.; Oerlemans, Simone; van de Poll-Franse, Lonneke V.; van Erning, Felice N.; van den Bos, Frederiek; Schuijtemaker, Johan S.; van den Berkmortel, Franchette W.P.J.; ten Bokkel Huinink, Daan; Hamaker, Marije E.; Dekker, Jan Willem T.; Wientjes, Caroline A.; Portielje, Johanna E.A.; et al.
Abstract: Background: Older patients who are functionally compromised or frail may be at risk for loss of quality of life (QoL) after colorectal cancer (CRC) surgery. We prospectively studied health-related QoL (HRQoL) and its association with functional dependency on multiple time points before and after CRC surgery. Methods: Included were patients aged 70 years and older who underwent elective CRC surgery between 2014 and 2015 in combination with an oncogeriatric care path. HRQoL (EORTC QLQ-C30 and CR38) and activities of daily living (ADL, Barthel Index) were measured at four time-points; prior to (T0) and at 3 (T3), 6 (T6), and 12 (T12) months after surgery. Functional dependency was defined as a Barthel Index <19. Using mixed-model regression analysis associations between dependency, time and HRQoL outcomes were tested and corrected for confounders. Results: Response rate was 67% (n = 106) to two or more questionnaires; 26 (25%) patients were functionally dependent. Overall, functionally independent patients experienced a higher HRQoL than dependent patients. Compared to T0, significant and clinically relevant improvements in HRQoL after surgery were observed in functionally dependent patients: better role functioning, a higher global health, a higher summary score, less fatigue and less gastrointestinal problems (p < .05). In functional independent patients, we observed no clinically relevant change in HRQoL. Conclusion: Colorectal surgery embedded in geriatric-oncological care has a positive impact on HRQoL in older functionally dependent patients with cancer. Moderate functional dependency should not be considered a generic reason for withholding surgical treatment. Information derived from this study could be used in shared decision making.